How does the English4IT Platform Provide English Materials for Computer Science Learners? - Puspa Fortuna Zulfa (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
During the COVID-19 pandemic, the learning process shifted from face-to-face to online learning. English4IT is one of the platforms that can support the success of the online learning process. This study aims to investigate and describe the use of the English4IT platform to assist the English learning process for computer science learners. The platform contains materials suitable for computer science learners’ needs, including vocabulary, four main English skills, and practical activities, either synchronous or asynchronous. This descriptive qualitative study gathered the data from the contents of the English4IT platform. The data were then analyzed qualitatively by applying the platform and comparing the findings with previous studies and existing theories. This study’s novelty lies in its originality since a deep investigation of this platform has not been conducted by any previous researchers. The findings indicated that the use of this platform could effectively assist the students in learning English and motivate them to join. Various materials provided adequate teaching materials and references for computer science learners. The activities could enhance the students’ progress in each skill, and the re-do feature made it easier for learners to correct their mistakes. This study implies that the English4IT platform is recommended as an alternative way to teach English to computer science students. Before using this platform, it is recommended to recognize the strengths and weaknesses so that the English teachers can use it effectively.